If at First You Do Succeed, Do You Try, Try Again? Developing the Persistence–Licensing Response Measure to Understand, Predict, and Modify Behavior Following Subgoal Success. (April 2019) - Zemack-Rugar, Yael; Corus, Canan; Brinberg, David
Following subgoal success at a long-term goal, consumers can persist, behaving consistently with the long-term goal, or license, behaving consistently with competing shorter-term goals. The authors extend prior work by proposing that this choice is driven, in part, by chronic differences in consumers' cognitive and emotional responses to subgoal success. In Studies 1–5, they develop and validate a measure that captures these individual differences: the Persistence–Licensing Response Measure (PLRM). They demonstrate that the PLRM predicts persistence and licensing where existing constructs and measures do not, showing that consumers' responses to subgoal success represent a unique dimension of self-regulation. In Studies 6–10, the authors demonstrate that the PLRM moderates the effect of subgoal success on persistence and licensing behavior, revealing that the same subgoal success situation can lead to systematically different behaviors. The authors also examine how marketing interventions can be used to increase consumers' persistence following subgoal success. This work furthers the understanding of the determinants of persistence and licensing, improves prediction of behavior, and offers marketers tools to segment and target consumers, increasing persistence in key goal domains.